Prevalence of Group B Streptococcus in high vaginal swab specimen at Universiti Kebangsaan Malaysia Medical Centre (UKMMC) / Nur Syahirah Lila Zam Zam - Lila Zam Zam, Nur Syahirah (2014)
The aim of the study was to determine the prevalence of Group B Streptococcus in a high vaginal swab specimen in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Group B Streptococcus (GBS), also known as ‘Streptococcus agalactiae’ is a gram positive streptococcus characterized by the presence of Group B Lancefield antigen. Group B Streptococcus is a part of normal flora of the gut and frequently colonizes the vagina of 20-40% women. Polysaccharide antiphagocytic capsule of GBS is the main virulence factor. Women with GBS colonization are at increased risk of GBS colonization in subsequent pregnancy. Group B Streptococcus also is an important cause of adult and neonates infection which required treatment with antibiotics. According to previous study, the prevalence of GBS was 30% among pregnant women. The study design was a retrospective study involving collection of high vaginal swab (HVS) data from January 2014 until April 2014 at UKMMC. The number of HVS samples positive with GBS in January, February, March and April were 44,51, 68 and 47 respectively. In UKMMC, Malay women had the highest percentage of HVS positive with GBS isolates 76.47%, while for Chinese and Indian were 16.18% and 3.90% respectively followed by others 3.45%. All isolates were sensitive to ampicillin and ceftriaxone but 76% resistant to bacitracin. Group B Streptococcus were 99%, 90% and 88% susceptible towards penicillin, erythromycin and clindamycin respectively. Our findings show that the prevalence of GBS positive isolates from January 2014 until April 2014 is 13.43%. This results was based on the total HVS sample collected from January until April 2014.